Profil Penalaran Siswa dalam Menyelesaikan Masalah Matematika - Wulandari, Yunita Oktavia; Prayitno, Anton; Raje, Modesta Iwanti; Octavianti, Cynthia Tri; Pratiwi, Ruvita Iffahtur (FKIP Universitas Wisnuwardhana, 2022)
This study aims to describe the reasoning of seventh grade students in solving mathematical problems which includes sense-making, conjecturing, convincing, reflecting, and generalizing reasoning components. Based on the research objectives, the research conducted is useful to provide an overview of students' abilities in solving math problems involving five components through data exposure and discussion can explain the differences in students' abilities made by students. This research uses qualitative research methods with descriptive research types and data analysis includes three stages, namely data reduction, data presentation, and conclusion drawing. The source of data in this study is the results of students' work on the problem of rectangular flat shapes given, with the subject chosen 3 students. Of the 3 students there are differences in ability in solving rectangular problems so that these differences are classified into 3 characteristics based on the abilities of each student in the form of 1 student with high mathematics ability, 1 student with moderate mathematics ability, 1 student with low mathematics ability.